Dynamics of heavy vibrating machines taking into account instability in time of their parameters. - Дирда, Віталій Ілларіонович; Dyrda, Vitalii; Лисиця, Микола Іванович; Lisitsa, Mykola; Лапін, Володимир Олексійович; Lapin, Volodymir; Агальцов, Генадій; Ahaltsov, Hennadii; Калганков, Євген Васильович; Kalgankov, Yevgen; Толстенко, Олександр Васильович; Tolctenko, Oleksandr; et al. (Національна академія наук Казахстану, 2020)
Underground mining of uranium ores consists of several technological processes, one of the most important of which is the release of broken rock from the working excavation zone and loading it into transportation vehicles. The issue of increas-ing the intensity of production requires a simulta-neous increase in the productivity of all produc-tion processes, including the production of miner-al raw materials. At the same time, it is necessary to create both a high-performance and a safe pro-cess. This problem is successfully solved by the use of vibration machines with elastic links made of elastomeric materials, which, along with an increase in productivity, can reduce energy con-sumption and the number of freezes. An integrat-ed approach was used, which includes analytical studies and results of industrial tests of vibratory feeders for underground mining and delivery of uranium ores and building materials. On the basis of the developed algorithm and synergistic model of fatigue microfracture of rubber links in vibrato-ry feeder, mathematical equations were obtained, which made it possible to describe dynamics of feeders with time-depending parameters; when solving the integro-differential equation of the oscillatory system, the dependence of the ampli-tude characteristics of the feeder on the time of its operation is obtained. An original algorithm and synergistic model were developed, and on their basis, a mathematical apparatus was created, which allowed determining change of amplitude of vibratory feeder oscillations during its opera-tion. On the basis of analytical calculations, a method was developed and introduced for predict-ing changes of parameters change of oscillation amplitudes of vibratory feeder used for under-ground mining and feeding of uranium ores.
Динаміка важких вібраційних машин з урахуванням нестабільності в часі їх параметрів.
Keywords: вібраційний живильник; vibratory feeder; вібрації; vibrations; синергетична модель; synergetic model; недостатність втоми; fatigue failure